MODEL PERTUMBUHAN IKAN BERONANG LINGKIS (Siganus canaliculatus) HASIL TANGKAPAN SERO DI PERAIRAN KEPULAUAN SELAYAR - Masyahoro, Abdul (FAPETKAN UNTAD, 2011)
The research was conducted to study the growth model of Siganus canaliculatus which was based on body length parameters. The research was done through survey which was initiated by measuring the body length of n fish samples drawn from N fish population. The size of fish population (N) was based on the fish basket times the number of fish in each basket for every landing catch. The number of fish sample required was based on variability of catch yield for each catching period. Data collected was analysed on the basis of functional relationship between fish fork length (FL) and body weight (W) following the non linear mathematical equation W (i) = qFL(i)b. A model simulation was then performed using the techniques of data interpolation and extrapolation. The regression coefficient value for the relationship of the two parameters was 2.4. indicated that the growth model of the Siganus canaliculatus was allometric. Key words: Allometric, extrapolation, interpolation, model, siganus canaliculatus, simulation.